the effect of using Polya strategy on the achievement of secondary school grade in chemistry . (Journal of the College of Basic Education, 2020)
The present research tackles the effect of using Polya strategy on the achievement of secondary school grade in chemistry .The research was limited to fourth year secondary female students /scientific branch in Al-Warka privet secondary school / Directorate General of Education / Al-Risafah 1for the academic year 2011/2012 which was intentionally chosen The sample of the research was 30 female students who were chosen randomly to represent the sample of the study. The number of Each group was 15 female students The sample of the research was The two groups were equalized on the following variables ( age ,achievement in chemistry of the third intermediate class and previous experiences) objective test was prepared which consisted of 20 items ten of them were multiple- choice and five of them were completion type and the other five were open- ended questions Face validity ensured by exposing the test to a jury of experts while content validity was ensured by preparing test map. Item difficulty discrimination power and function of distracters were calculated .the reliability of the objective items were calculated by using Kuder-Richardson formula. The reliability estimate was (0.80). The reliability of open-ended questions was secured by the agreement the scorers. The researcher and the teacher of the subject scored the test The two sets of the scores were correlated by using Pearson correlation –coefficient and reliability index was (0,83) which is regarded high correlation. The results show statistically significant difference on achievement for the experimental group . The study recommended several recommendations, including the need to adopting new teaching strategies.